Practical economics : an introduction - Shade, E. D. 1943- (Prentice Hall, 1999)
This book provides a sound background in economics for the general reader. It presents both microeconomics (studying the behaviour of individual consumers, firms and industries) and macroeconomics (studying outcomes for the whole economy).